2018
DOI: 10.1055/s-0038-1670659
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Coagulant and Pro-Thrombotic Effects of Paclitaxel Mediated by Red Blood Cells

Abstract: Background Paclitaxel is one of the most widely used anti-cancer drugs, but numerous case reports of thrombotic events in the cancer patients using paclitaxel raise concern over its pro-thrombotic risk. Materials and Methods We investigated whether paclitaxel can elicit pro-thrombotic properties in red blood cells (RBCs) through phosphatidylserine (PS) exposure and microvesicle (MV) release. Results In freshly isolated human RBCs, paclitaxel induced thrombin generation through PS exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A previous study (Chung et al., 2007) demonstrated that paclitaxel could induce pro‐coagulant activity in red blood cells through phosphatidylserine exposure and micro‐vesicle release, which could ultimately increase the thrombotic risk. In addition to increasing thrombin generation, paclitaxel could also promote adhesion between red blood cells and endothelial cells as well as aggregation of red blood cells (Kim et al., 2018). As docetaxel has a similar mechanism of action to paclitaxel, it may contribute to thrombosis via the above mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (Chung et al., 2007) demonstrated that paclitaxel could induce pro‐coagulant activity in red blood cells through phosphatidylserine exposure and micro‐vesicle release, which could ultimately increase the thrombotic risk. In addition to increasing thrombin generation, paclitaxel could also promote adhesion between red blood cells and endothelial cells as well as aggregation of red blood cells (Kim et al., 2018). As docetaxel has a similar mechanism of action to paclitaxel, it may contribute to thrombosis via the above mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel, an established anticancer drug increases PS exposure in RBC that leads to blood coagulation and thrombosis. However, if it leads to over expression of any specific scramblase, remains to be determined ( Kim et al, 2018 ). Synthetic enzyme made from eight DNA strands induces scrambling of ∼ 10 7 lipids in biological membranes.…”
Section: Transcriptional Regulation Of Scramblase Expression During M...mentioning
confidence: 99%
“…Paclitaxel,an alkaloid from Pacific yew tree ( Taxus brevifolia ) stimulates PS exposure in RBCs that leads to blood coagulation and thrombosis ( Kim et al, 2018 ). Paclitaxel induced 60% increase in apoptosis and G2/M phase cell-cycle arrest in Canine mammary cancer cells by down regulating Bcl-2 and up regulating Bax ( Ren et al, 2018 ).…”
Section: Role Of Scramblases In Tme Signalingmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), with an over 2000 year history in the treatment of diseases, is a valuable source for drug leads and candidates in the process of drug discovery. Many popular natural compounds, such as artemisinin, berberine, ginkgolide, and paclitaxel, extracted from TCMs, play an important role in disease treatments [10,11,12,13]. In this work, a combined approach involving docking-based virtual screening and bioassay-based validation was performed to identify natural Syk small molecule inhibitors from TCMs.…”
Section: Introductionmentioning
confidence: 99%